Antwoord:
Zie onder.
Uitleg:
- # X² + 5x + 6 = 0 # kan worden geschreven als
# X ^ 2 + 3x + 2x + 6 = 0 #
of #x (x + 3) 2 (x + 3) = 0 #
of # (X + 2) (x + 3) = 0 #
dat wil zeggen ofwel # X + 2 = 0 # middelen # X = -2 # of # X + 3 = 0 # middelen # X = -3 #
- # X² = 4x-5 # kan worden geschreven als
# X ^ 2-4x + 5 = 0 #
of # (X ^ 2-4x + 4) + 5-4 = 0 #
of # (X-2) ^ 2 + 1 = 0 #
of # (X-2) ^ 2-i ^ 2 = 0 #
of # (X-2 + i) (x-2-i) = 0 #
dat wil zeggen ofwel # X = 2-i # of # X = 2 + i # - Hier is oplossing complexe getallen.
- # X² + 4x-12 = 0 # kan worden geschreven als
# X² + 6x-2x-12 = 0 #
of #x (x + 6) 2 (x + 6) = 0 #
of # (X-2) (x + 6) = 0 #
d.w.z. # X = 2 # of # X = -6 #
- # 3x² + 6x = 0 # kan worden geschreven als
# 3x (x + 2) = 0 #
dat wil zeggen ofwel # X = 0 # of # X = -2 #
- # 4x² + 9 = 12x # kan worden geschreven als
# 4x ^ 2-12x + 9 = 0 #
of # (2x) ^ 2-2xx2x xx3 + 3 ^ 2 = 0 #
of # (2x-3) ^ 2 = 0 #
d.w.z. # 2x-3 = 0 # of # X = 3/2 = 1,5 #